2010
DOI: 10.1111/j.1399-3062.2010.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

A very early and acute renal impairment due to polyomavirus allograft nephropathy

Abstract: Polyomavirus-associated nephropathy (PVAN) has become an important cause of graft loss in the last few years. The typical course of PVAN is characterized by an asymptomatic period of viruria followed, within weeks, by the development of viremia in the context of stable renal function. The persistence of viral replication characterized by high viremia, leads to parenchymal injuries and causes the development, within months, of PVAN that could lead to deterioration in graft function and graft loss. We reported, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Renal dysfunction develops slowly and permanent renal damage has already developed when the creatinine levels are increased. However, Comai et al have reported a case of BKVN presenting with acute kidney injury after renal transplantation (10).…”
Section: Introductionmentioning
confidence: 99%
“…Renal dysfunction develops slowly and permanent renal damage has already developed when the creatinine levels are increased. However, Comai et al have reported a case of BKVN presenting with acute kidney injury after renal transplantation (10).…”
Section: Introductionmentioning
confidence: 99%